Cooperate, Read, Repeat: Maximizing Resources and Student Potential in Intervention - Deegan, Joseph P. (My University, 2018)
70% of fourth grade students in the United States are either at, or below the basic proficiency (NAEP, 2011). As support in the research literature for early intervention to prevent such outcomes continues burgeoning, it is a necessity that schools have in place practices that are able to meet the needs of these struggling readers. Considering that the skill of reading fluency is one of the best known early predictors of successful reading, this seems like a particularly important academic skill to target (NRP, 2000). Adult-led repeated reading interventions are effective methods to improve reading fluency, but such interventions are costly to provide in terms of resources (Therrien, 2004). Already, 6% of an average elementary school day is spent on Social Studies and Science, 16% is spent on Mathematics, and approximately 40% of the day is spent on literacy instruction (US DOE, 1997). In light of the number of students still needing reading support, schools are in need of literacy programs that maximize effectiveness with minimal resources. Though the literature indicates that such reading interventions can be provided in a small group, there is a gap in the literature regarding whether the effectiveness of small group reading interventions would be impacted by altering the intervention focus from individual to group growth. The purpose of the current study is to address that gap. The current study provided student dyads with a reading intervention that initially targeted individual reading growth. After four weeks, the treatment variable of having students work toward a group growth goal was implemented in a multiple-baseline format over the course of twenty intervention sessions. Taken together, no significant differences were found in reading growth. However, across phases, students did exceed expectations in reading growth, indicating that the current intervention is likely to be efficacious regardless of goal orientation.
Keywords: Reading (Elementary)--Ability testing; Reading (Primary)--Remedial teaching; Oral reading--Study and teaching (Elementary); Reading (Elementary)